Human induced pluripotent stem cells as a disease model system for heart failure - Deicher, Anton; Seeger, Timon (Current heart failure reports, 2021)
Heart failure is among the most prevalent disease complexes overall and is associated with high morbidity and mortality. The underlying aetiology is manifold including coronary artery disease, genetic alterations and mutations, viral infections, adverse immune responses, and cardiac toxicity. To date, no specific therapies have been developed despite notable efforts. This can especially be attributed to hurdles in translational research, mainly due to the lack of proficient models of heart failure limited translation of therapeutic approaches from bench to bedside.